DISCOUNTED SERVICES AGAIN: THE HOMOGENEITY PROBLEM. - Thomas, Arthur L. (The Accounting Review, 1964)
Abstract In the article, the author attempts various aspects about valuation of assets in terms of the net discounted cash flows that they are expected to generate over their productive lives. While there may be much to be said for modifying some features of conventional accounting, this article attempted to show that the discounted services approach was a snare in the way toward improvement as it suffered from crippling internal weaknesses. The author has also argued that whenever a stream of cash flows is jointly generated by more than one asset, the discounted services method cannot be used to value those assets individually without becoming very arbitrary. From a study, it seems that most actual relationships between assets and net receipts would be nonhomogeneous and that few companies would be able to escape the severe flaws of the discounted services approach. Outside of financial accounting, the discounted services approach is largely unaffected by these arguments. The approach breaks down only when it is used to value individual assets for balance sheet purposes.